Effect of screw access hole or vent hole opening strategies on the adhesive filling rate of oral implant cement-retained posterior crowns. - Long Li; Xiaodong Sun; Huangjun Zhou; Min Liu; Cai Wen (PLoS ONE)
Purpose This study investigated the adhesive filling rate (AFR) of implant prostheses on the abutment shoulder and axial surfaces under various hole opening strategies,and examined the correlation between hole openings and permanent adhesive retention strength. Methods Implant crowns were divided into five groups: No hole (NH); Occlusal regular hole (ORH: 2.5 mm); Occlusal mini-hole (OMH: 1 mm); Lateral upper mini-hole (LUMH: 1 mm); and Lateral down mini-hole (LDMH: 1 mm). In the AFR experiment, abutments and prostheses were connected with two-color silicone rubber; the coverage of rubber at the inner surface of the prostheses was photographed. Images were analyzed by ImageJ software. In the adhesive retention strength experiment, prostheses and abutments were bonded using permanent resin cement; retention strength was measured using a universal testing machine. Data were analyzed using one-way analysis of variance (ANOVA) or Welch's ANOVA, followed by Tukey's honestly significant difference test. Results Abutment shoulder AFRs were OMH (98.70 ± 0.42%), LDMH (98.40 ± 1.30%), LUMH (97.92 ± 1.33%), NH (93.99 ± 5.45%), and ORH (86.11 ± 4.90%). One-way ANOVA revealed significant difference among groups (p < 0.001). Axial AFRs were LUMH (99.2 ± 0.47%), ORH (98.3 ± 0.8%), OMH (98.1 ± 0.5%), LDMH (97.9 ± 1.06%), and NH (96.4 ± 4.5%),Welch's ANOVA indicated no significant difference between groups (p = 0.054). In the retention strength experiment, OMH had the highest retention force (369.58 ± 27.27 N), whereas ORH had the lowest (272.81 ± 41.43 N), showing significant differences (p = 0.002). Conclusions Implant screw access hole or vent hole opening strategies affected AFR of implant cement-retained posterior crowns. Larger holes or no openings decreased AFR at the abutment shoulder, whereas axial AFR was less affected. Hole openings variations on implant cement-retained posterior crowns might also influence their retention strength.